PENGEMBANGAN MODUL PERMAINAN TRADISIONAL GUNA MENUMBUHKAN KARAKTER TOLERAN ANAK USIA 6-8 TAHUN - Benedicta Rani Nugraheni; Gregorius Ari Nugrahanta; Irine Kurniastuti (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aimed to develop a traditional game module, to determine the effectiveness of the use of traditional games to foster a tolerant character and to find out the quality of traditional game modules for children aged 6-8 years old. The method used in this research was research and development (R&D). This study involved five teachers in each district in Yogyakarta for gaining the needs analysis, four experts for expert judgment, and six children for limited experiment. The results showed: 1) The module was developed using ADDIE steps. 2) The quality of the module obtained a score of 3.43 which was included in the qualification of